Analisis Kualitas Raw Mix dan Optimasi Raw Mill Unit 5 R2 Produksi di PT. Semen Padang Indarung V - Fithry, Dwi Annisa; Parmanoan, Durain; Emal, Dini Aulias Sari; Rahmad, Alfein; Batubara, Riski Pathia Mulia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In making cement, of course, it has to go through processes that the factory. One of the processes in making cement is grinding and drying raw materials, namely the Raw Mill. Raw Mill is the initial stage in making Raw Mix where in the Raw Mill milling, drying, mixing, and separating materials such as limestone, silica, clay, and iron sand occur. Raw Mix is the main ingredient in making clinker which is the main raw material in making cement. The quality of the Raw Mix is very influential in making cement. Where in the process of making this Raw Mix there are changes in quality. Therefore, researchers want to know the main problems that exist in the differences in the quality of different Raw Mixes. In this case, researchers found several problems, including the quality of the raw materials in storage which was not good, then there were problems in the Raw Mill itself, where there were several inner mill parts that were experiencing wear and tear and had to be replaced. After being replaced, the quality of the Raw Mix is obtained which meets the standards and the total balance value of the Mass Balance is 606124.31 tonnes/hour and the total heat lost is 0.071 KJ.